Diagnosis dan Pengobatan Babesiosis pada Anjing Shih-Tzu di Klinik Lilipoet, Yogyakarta, Indonesia - Nabilah Putroe Agung; Dwi Priyowidodo; Ida Tjahajati; Lily Gunawan (Jurnal Sain Veteriner, 2022)
Dogs are one of the pet animals that have a loyal nature and are widely cared for in the community. It is not uncommon for dogs to often play in parks or outdoor environments that are surrounded by grass to play with their owners. The grass is a breeding ground for ticks, which can be vectors of disease carriers for dogs. Babesiosis is a disease caused by Babesia sp. and is transmitted by tick vectors. In this paper, we will discuss the clinical condition, diagnosis, and treatment of one dog with babesiosis at the Lilipoet clinic, Yogyakarta. A Shih-Tzu dog has clinical symptoms of fever with a temperature of 39.9oC, decreased appetite, and has a history of yellow vomiting, and found one tick. Blood was collected for microscopic examination of blood smears, blood hematologic, and molecular examination. Hematologic examination of the blood showed the value of thrombocytopenia with a value of 32 x 103/µL. Molecular examination with Polymerase Chain Reaction (PCR) showed positive results of Babesia sp. with visible DNA bands at 490bp. Treatment was carried out by giving one dose of antiprotozoal diminazen aceturate 3.5 mg/kg BW and doxycycline 10mg/kg BW once a day for 14 days.